O?imieniu Stanisław słów kilka = A?Few Words about the Name Stanisław - Żuraszek-Ryś, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Stanisław is the name of Slavonic origin representing its own, native system of naming people. It came from the proto-Slavonic epoch and referred to Indo-European naming systems. It is a compound name based on two lexemes: Stani- (root of the verb stand) + -sław "fame".
Keywords: antroponimia; polski system nazewniczy; anthroponomastics; system of naming people in Poland